The constructed identities of women in unconventional relationships and the domestic violence law in India : towards a more feminist legal framework - Puthuran, Anna V. (2012)
The Indian legal system has been dealing with the problem of domestic violence in the recent years especially since the advent of the new legislation the Protection of Women from Domestic Violence Act, which was brought into effect from the 26th of August, 2006. The original contribution that this thesis makes to knowledge is that it identifies a potential category of users of this law- Women in Unconventional Relationships (WUR), and tests the support systems and the ease of access available to this category of women within two different domestic violence frameworks in India. This thesis locates the constructions of transgressive WUR identities in history, society and theoretical discourse and investigates whether these constructions adversely affect their legal subjectivity under the domestic violence law in India. It locates WUR within the domestic violence framework in Delhi, named the Victim Model for the purposes of this research, and within the Survivor Model in Mumbai. It privileges the voices of ten WUR who articulate their experiences of survival, domestic violence and the law. The research uses a combination of inter-subjective reflexive research and a feminist analysis of the domestic violence framework. The constructions of identities and the levels of transgression that take place and its effects on survivor/victim legal agency are investigated. The thesis identifies the best domestic violence framework suited for WUR which encourages their rights-bearing capacity as full-fledged citizens of the Indian state.